Titanium Dioxide Nanoparticle: A Comprehensive Review on Synthesis, Applications and Toxicity - Rakhi Chandoliya; Shivika Sharma; Vikas Sharma; Rohit Joshi; Iyyakkannu Sivanesan (Plants)
Nanotechnology has garnered significant interest worldwide due to its wide-ranging applications across various industries. Titanium dioxide nanoparticles are one type of nanoparticle that is commonly utilised in everyday use and can be synthesized by different techniques using physical, chemical and biological extracts. Green synthesis is an economical, environmentally benign and non-toxic method of synthesising nanoparticles. Titanium dioxide nanoparticles have a positive impact on plant physiology, particularly in response to biotic and abiotic stresses, depending on various factors like size, concentration, exposure of the nanoparticles and other variables. Further, titanium dioxide nanoparticles have many applications, such as being used as nano-fertilizers, adsorption of heavy metal from industrial wastewater and antimicrobial activity, as discussed in this review paper. Previous studies investigated whether titanium dioxide nanoparticles also induce genotoxicity may be due to mishandling procedure, exposure time, size, concentration and other variables. This is still contradictory and requires more research. The present review is a pragmatic approach to summarize the synthesis, application, nanotoxicity, genotoxicity and eco-friendly method of nanoparticle synthesis and disposable.